Studies on isolation and characterisation and its effect of seed inoculation of PGPR (Pseudomonas fluorescens) on yield of tomato - B. Karthikeyan, U. Sakthivel, S. Mahalakshmi (Journal of Phytology, 2009)
Soil samples of five different locations of rhizosphere of tomato.Ã‚Â The sample used for identification of Pseudomonas fluorescens and characterisation based on biochemical characteristics.Ã‚Â The best isolate PF-5 used for seed treatment of with tomato variety PKM-1.Ã‚Â The higher fruit yield was recorded in the triple combination of Pseudomonas fluorescens + Azotobacterchroococcum + Azospirillum brasilense @ 900g/plant-1 followed by Pseudomonas + Azotobacter.